Online learning during covid-19 lockdown: a study regarding portuguese public higher education students - Morais, Nídia Salomé (2022)
In March 2020, the face-to-face presential model of higher education classes was suspended in Portugal due to the COVID-19 pandemic, which forced all educational institutions to shift to fully online learning solutions. This scenario posed enormous challenges to institutions, teachers, and students to allow the continuity of teaching activities in the period left for the conclusion of the 2nd semester of the academic year 2019/2020. The remaining of the semester attended from home due to the confinement measures, and typical classroom teaching models were not a viable solution. In this paper, we present some of the results gathered through a questionnaire covering several issues related to students' perceptions about their experience in a particular curricular unit during this period. The sample comprises 22 students attending the 2nd year of an undergraduate communication program during the second semester of the 2019/2020 academic year. The results obtained reveal that the students adapted well to the entirely at a distance e-learning modality. Many revealed that it was sometimes challenging to manage their own time because they were always at home in the same environment. The vast majority managed to overcome the difficulties of accessing specific software because Adobe allowed access to temporary licenses for education purposes. As to technical difficulties, only one student could not complete the proposed tasks within the defined deadlines on account of hardware problems. The majority referred to temporal flexibility as one of the positive aspects, mainly because they were not limited to the class's time slot and physical space.